A Novel Interfragmentary Technique vs. A Conventional Posterolateral Approach for Unstable Femoral Intertrochanteric Fractures in the Elderly: A Retrospective Cohort Study - Hakan Zora; Gökhan Bayrak; Ömer Faruk Bilgen (Medicina)
Background and Objectives: Intertrochanteric fractures of the femur are common in the elderly due to the increase in longer life expectancy. However, unstable intertrochanteric fractures in the elderly population were still a significant concern for the postsurgical period after total hip arthroplasty (THA). This study aimed to compare the demographics, operative time, dislocation rate, and length of stay of the novel interfragmentary technique (IFT) and the conventional posterolateral approach (CPA) for unstable intertrochanteric femoral fractures treated with THA in the elderly. Materials and Methods: This retrospective study investigated community-dwelling elderly patients with type III, IV, and V unstable femoral intertrochanteric fractures according to the Evans–Jensen classification, treated with THA by a well-experienced single surgeon. The patients were separated into IFT (n = 74) and CPA (n = 67) groups. Patient demographics (age, gender, and body mass index), total surgical duration, dislocation rates, length of stay and follow-up, and complication rates were recorded. Results: The mean age was 80.37 years in the IFT and 80.14 in the CPA groups (p = 0.838). Body mass index, gender, complication, and revision rates did not differ between groups (p > 0.05). The mean follow-up of the IFT group was 4.15 years, and 10.25 years in the CPA group (p = 0.001). Total surgical duration was comparable, with 69.98 min in the IFT group and 69.55 min in the CPA group (p = 0.697). The dislocation rate was 2.7% (n = 2) in the IFT group and 9% (n = 6) in the CPA group (p = 0.109). The mean length of stay was 66.97 h in the IFT group and 67.83 h in the CPA group (p = 0.729). Conclusions: The interfragmentary surgical technique, a novel technique for unstable intertrochanteric fracture surgery, shows promising clinical outcomes. Preserving the short rotator muscles and posterior capsule utilizing the novel IFT can be advantageous for the risk of dislocation without increasing surgical duration. It can be concluded that performing THA using IFT emerges as a practical and viable procedure for treating unstable intertrochanteric fractures in elderly patients.